2000
DOI: 10.1001/archinte.160.17.2653
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Utilization in Chronic Obstructive Pulmonary Disease

Abstract: Health care utilization among COPD patients is approximately twice that of age- and sex-matched controls, with much of the difference attributable to smoking-related diseases. In this health maintenance organization, inpatient costs were similar to and outpatient costs were much higher than national averages for COPD patients covered by Medicare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(88 citation statements)
references
References 27 publications
9
69
0
1
Order By: Relevance
“…Respiratory system disorders were the principal discharge diagnosis, but cases with COPD had a higher proportion of discharge diagnoses than controls in almost every major diagnosis category. Admissions for cardiovascular diseases, the leading discharge diagnosis category in controls, were almost twice as common among COPD cases [64].…”
Section: Direct and Indirect Costsmentioning
confidence: 97%
“…Respiratory system disorders were the principal discharge diagnosis, but cases with COPD had a higher proportion of discharge diagnoses than controls in almost every major diagnosis category. Admissions for cardiovascular diseases, the leading discharge diagnosis category in controls, were almost twice as common among COPD cases [64].…”
Section: Direct and Indirect Costsmentioning
confidence: 97%
“…[3839] Systemic inflammation is probably an important contributory factor responsible for both COPD and diabetes mellitus. The nurses’ healthy study: a prospective study over an 8-year period had showed that COPD patients have a 1.8% relative risk of developing diabetes.…”
Section: Copd and Individual Components Of The Metabolic Syndromementioning
confidence: 99%
“…Smoking cessation in the COPD patient reduces respiratory symptoms, and is associated with improvement in health-related quality of life and increased survival [5,6,7,8]. Despite the benefits of smoking cessation, 36%–46% of adults with COPD are current smokers [4,9,10,11]. …”
Section: Introductionmentioning
confidence: 99%